Strategi Mix Marketing dalam Meningkatkan Minat Siswa Masuk Man 1 Musi Banyuasin - Adhelmi Adhelmi; Muhammad Win Afgani; Afriantoni Afriantoni (Departement of Mathematics Education, 2024)
This study aims to find out the mix marketing strategy in increasing students' interest in entering MAN 1 Musi Banyuasin. This study uses a type of qualitative research that is descriptive. The subjects of this research are teachers and students. The data collection techniques used in this study are observation, interviews and documentation. Based on the results of the study, it can be concluded that MAN 1 Musi Banyuasin has successfully implemented a marketing mix strategy as an effort to recruit students to enter MAN 1 Musi Banyuasin. The increase in the number of students is sufficientsignifikan every year by implementing a marketing mix (7P) strategy consisting of product, price, place, promotion, people (HR), physical evidence, and process. The products offered are in accordance with the needs of the community with free education fees. The strategic location is on the Sarangan highway, close to several government agencies. Promotion is carried out in the form of advertising (social media and print media), public relations, word of mouth and direct marketing. The human resources owned are quite qualified and continue to develop by participating in trainings.